Taxation and fiscal reform in Ghana - Tony Addison; Robert Osei (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
To finance basic pro-poor services, the Government of Ghana must mobilize more public revenue. But tax reform has been highly controversial in Ghana. An attempt to introduce VAT in 1995 failed after widespread protests. Although a second attempt to introduce VAT in 1998 succeeded, strong resistance to tax reform remains, and the total tax base remains narrow and over-dependent on petroleum taxes. This paper argues that slow progress in public expenditure reform, in particular in raising spending on basic services, has impeded the public's willingness to pay taxes, since many people see little benefit. This is especially the case in the poorer regions, which in addition have borne the brunt of the rising petroleum tax. The paper concludes that much more attention must be given to the political economy of fiscal policy in Ghana, if lasting improvements to the fiscal system are to be achieved.
Keywords: O23; O55; H20; 330; fiscal policy; taxation; Ghana; sub-Saharan Africa; Finanzpolitik; Steuer; Ghana